Analyse de la pluralité des savoirs enseignés lors d’une séquence de jeux sportifs collectifs à l’école primaire - Christine Amans Passaga; Odile Devos-Prieur (Recherches en Éducation)
The study consists of a didactic approach to a Physical Education and Sports (EPS) teaching cycle conducted by a primary school teacher (PE). The purpose is to update the type of curriculum taught for physical activity and sports through observations made during hockey lessons. The study is based on an analysis of various levels of declared and actual practices. It provides an update to the content adaptation to be undertaken by the teacher to provide real-time adjustments and the teaching methods she uses to engage the students in the lessons.